Pengaruh Persepsi Merek dan Kualitas Produk Terhadap Kepercayaan Merek Produk Jinawi di Kota Malang - Putri Febrianti Nufita Sari; Ita Rifiani Permatasari; Mohammad Maskan (Indo Publishing, 2026)
This research aims to determine and analyze the effect of Brand Perception and Product Quality on Brand Trust in Jinawi products in Malang City. The population in this study are consumers who have purchased Jinawi products. This research applies a quantitative method with an explanatory research approach through a purposive sampling method with a total analyzed sample of 94 respondents. The results of multiple linear regression analysis and hypothesis testing indicate that Brand Perception (X1) and Product Quality (X2) partially and simultaneously have a positive and significant effect on Brand Trust (Y). Furthermore, the product quality variable (X2) is concluded to have the largest contribution to brand trust (Y) compared to the Brand Perception variable (X1). For future research, it is recommended to expand the scope of the research population to cover a wider area, and add other variables to obtain a more comprehensive understanding of the factors that potentially affect Brand Trust, such as customer satisfaction, customer loyalty, or customer experience.